Pulmonary effects of dexmedetomidine infusion in thoracic aortic surgery under hypothermic circulatory arrest: a randomized placebo-controlled trial - Seongsu Kim (Nature Portfolio, 2021)
Abstract Dexmedetomidine has emerged as a promising organ protective agent. We performed prospective randomized placebo-controlled trial investigating effects of perioperative dexmedetomidine infusion on pulmonary function following thoracic aortic surgery with cardiopulmonary bypass and moderate hypothermic circulatory arrest. Fifty-two patients were randomized to two groups: the dexmedetomidine group received 1 µg/kg of dexmedetomidine over 20 min after induction of anesthesia, followed by 0.5 µg/kg/h infusion until 12 h after aortic cross clamp (ACC)-off, while the control group received the same volume of normal saline. The primary endpoints were oxygenation indices including arterial O2 partial pressure (PaO2) to alveolar O2 partial pressure ratio (a/A ratio), (A–a) O2 gradient, PaO2/FiO2 and lung mechanics including peak inspiratory and plateau pressures and compliances, which were assessed after anesthesia induction, 1 h, 6 h, 12 h, and 24 h after ACC-off. The secondary endpoints were serum biomarkers including interleukin-6, tumor necrosis factor-α, superoxide dismutase, and malondialdehyde (MDA). As a result, dexmedetomidine did not confer protective effects on the lungs, but inhibited elevation of serum MDA level, indicative of anti-oxidative stress property, and improved urine output and lower requirements of vasopressors.